2013
DOI: 10.1093/molbev/mst260
|View full text |Cite
|
Sign up to set email alerts
|

Neanderthal Introgression at Chromosome 3p21.31 Was Under Positive Natural Selection in East Asians

Abstract: Studies of the Neanderthal and Denisovan genomes demonstrate archaic hominin introgression in Eurasians. Here, we present evidence of Neanderthal introgression within the chromosome 3p21.31 region, occurring with a high frequency in East Asians (ranging from 49.4% to 66.5%) and at a low frequency in Europeans. We also detected a signal of strong positive selection in this region only in East Asians. Our data indicate that likely candidate targets of selection include rs12488302-T and its associated alleles--am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
3
12

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 43 publications
3
53
3
12
Order By: Relevance
“…W 2013 r. Ding i wsp. [10] odkryli u mieszkańców Azji Wschodniej wysoką częstość neandertalskiego introgresywnego haplotypu o długości ok. 200 tys. par zasad (pz) na chromosomie 3p21.31.…”
Section: Wstępunclassified
See 2 more Smart Citations
“…W 2013 r. Ding i wsp. [10] odkryli u mieszkańców Azji Wschodniej wysoką częstość neandertalskiego introgresywnego haplotypu o długości ok. 200 tys. par zasad (pz) na chromosomie 3p21.31.…”
Section: Wstępunclassified
“…Region ten obejmował loci 18 genów, w tym loci genów: HYAL1, HYAL2 i HYAL3 kodujących odpowiednio: typ 1, typ 2 i typ 3 enzymu hialuronoglukozoaminidaza (hialuronidaza, EC 3.2.1.35), który depolimeryzuje kwas hialuronowy. Według tych autorów bardzo ścisłe sprzężenie swoistej dla neandertalskiego haplotypu w Eurazji transwersji g.50318299T>G (rs35455589) genu HYAL2 (c.1252A>C, p.Ile418Leu) z polimorfizmem rs11130248 (g.50314769A>G) predysponującym do bliznowca u Japończyków [11] sugeruje jej związek z ryzykiem bliznowca również w populacji kontynentalnej Azji Wschodniej [10].…”
Section: Wstępunclassified
See 1 more Smart Citation
“…For example, genes involved in functions related to keratin filaments, sugar metabolism, muscle contraction, body fat distribution, enamel thickness and oocyte meiosis have been targeted by adaptive introgression from Neanderthals Racimo et al, 2017;Zanolli et al, 2017). Genes involved in the variation of skin pigmentation and hair morphology (BNC2, MC1R) also show the signature of positive selection as the result of adaptation to diverse habitats with different degree of insolation (Dannemann & Kelso, 2017;Ding et al, 2014;Frost et al, 2017). Advantageous immune variants introduced into the modern human population from archaic genomes have substantially contributed in the present-day diversity of immune genes (Mendez et al, 2012;Mendez et al, 2013;Nédélec et al, 2016;Quach et al, 2016;Racimo et al, 2015).…”
Section: Genomic Signatures Of Adaptive Introgression From Archaic Tomentioning
confidence: 99%
“…Many studies have found evidence for "adaptive archaic introgression" [87][88][89][90][91][92]. Since the advent of whole genome sequencing, evidence has emerged that there was admixture between humans and two archaic hominids, Neanderthals [33,93,94] and Denisovans [95,96].…”
Section: Analysis Of Archaic Introgressionmentioning
confidence: 99%